EKSPRESI KEBEBASAN DAN TANGGUNG JAWAB PEREMPUAN DALAM NOVEL PAYA NIE KARYA IDA FITRI (KAJIAN PSIKOLOGI SASTRA JEAN PAUL SARTRE) - Fiah Luthfiah Bani; Andi Karman; Aslan Abidin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the expressions of freedom and responsibility of female characters in the novel Paya Nie by Ida Fitri through a literary psychology approach with the existentialism perspective of Jean-Paul Sartre. The novel is analyzed to express women’s life experiences within social contexts such as poverty, social pressure, and conflicts in Acehnese society. This study employs a descriptive qualitative method with thematic analysis techniques on data in the form of narration, dialogue, and monologue of female characters in the novel. The data were collected through intensive reading, note-taking, and classification of relevant excerpts based on the research focus.The results show that the expressions of freedom of female characters are manifested in two forms: freedom in speech and freedom in action. Freedom in speech is reflected in the characters’ courage to express opinions and make life choices, while freedom in action is demonstrated through their responses to the social situations they face. This study also finds expressions of responsibility shown by female characters in both speech and action, such as their concern for family and awareness in carrying out social roles. The findings indicate that the freedom of female characters in the novel Paya Nie is inseparable from the responsibilities they must bear as consequences of the life choices they make.